Australia burning : fire ecology, policy and management issues - Cary, Geoffrey; Lindenmayer, David; Dovers, Stephen (CSIRO ; Eurospan, 2003)
The phenomenon of fire in the Australian landscape traverses many interests and disciplines. At a national level, there is an urgent need for the integration of both the natural and social sciences in the formulation of public policy.